Effects of Strength Training Associated With Whole-Body Vibration Training on Running Economy and Vertical Stiffness. Issue 8 (August 2015) - Roschel, Hamilton; Barroso, Renato; Tricoli, Valmor; Batista, Mauro A.B.; Acquesta, Fernanda M.; Serrão, Júlio C.; Ugrinowitsch, Carlos
Abstract : Abstract: Roschel, H, Barroso, R, Tricoli, V, Batista, MAB, Acquesta, FM, Serrão, JC, and Ugrinowitsch, C. Effects of strength training associated with whole-body vibration training on running economy and vertical stiffness. J Strength Cond Res 29(8): 2215–2220, 2015—Running economy (RE) is defined as the energy cost to maintain a submaximal running velocity and seems to be affected by individual's neuromuscular characteristics, such as stiffness level. Both resistance training (RT) and whole-body vibration training added to RT (WBV + RT) have been shown to influence those characteristics. Thus, it is conceivable that RT and WBV + RT could also affect RE. The objective of this study was to investigate if a 6-week training period of RT and WBV + RT influences RE and vertical stiffness (VS). Fifteen recreational runners were divided into RT or WBV + RT groups. Running economy, VS, and lower-limb maximum dynamic strength (1 repetition maximum [1RM] half-squat) were assessed before and after the 6-week training period. There was a main time effect for 1RM, but no other statistically significant difference was observed. Neither conventional RT nor RT performed on a WBV platform improved VS and RE in recreational long distance runners. It is possible that movement velocity was rather low, and utilization of stretch-shortening cycle might have been compromised, impairing any expected improvement in RE.